Intuitionistic Fuzzy Calculus - Lei, Qian.; Xu, Zeshui; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a comprehensive and systematic review of the latest research findings in the area of intuitionistic fuzzy calculus. After introducing the intuitionistic fuzzy numbers' operational laws and their geometrical and algebraic properties, the book defines the concept of intuitionistic fuzzy functions and presents the research on the derivative, differential, indefinite integral and definite integral of intuitionistic fuzzy functions. It also discusses some of the methods that have been successfully used to deal with continuous intuitionistic fuzzy information or data, which are different from the previous aggregation operators focusing on discrete information or data. Mainly intended for engineers and researchers in the fields of fuzzy mathematics, operations research, information science and management science, this book is also a valuable textbook for postgraduate and advanced undergraduate students alike.
1 Basic Concepts Related to Intuitionistic Fuzzy Numbers -- 2 Derivatives and Differentials of Intuitionistic Fuzzy Functions -- 3 Integrals of Intuitionistic Fuzzy Functions -- 4 Aggregation Operations of Continuous Intuitionistic Fuzzy Information -- 5 Relationships among IFWA Operator, IFIA Operator and Definite Integrals of IFFs -- 6 Complement Theory of Intuitionistic Fuzzy Calculus -- References. .
Keywords: Computational intelligence; Operations research; Management science; Computer science -- Mathematics; Mathematical statistics; Computational Intelligence; Operations Research, Management Science; Operations Research and Decision Theory; Probability and Statistics in Computer Science